(untitled) (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
unstable global climate change, sea waves can damage coastal areas and buildings surrounding. Wave dampers are needed to reduce the energy of incident waves and reflected waves excessive and undesirable in water areas. The effectiveness of wave dampers for sloping beach types and porous parabolas to dampen reflected water waves are the objectives of this study. This research carried out at the Marine Technology Research Laboratory, Hasanuddin University. Regular waves are tested in wave flume with a length of 25 m, a width of 1 m and a depth of 1.2 m which is equipped with a wave generator flaps type. The wave absorbers at the other end are made of 20 cm thick foam and mounted on porous steel cross-section with a porosity of 0.155091. The eight wave probe points are placed together along the length wave flume. Wave probe 8 is placed as far as the wavelength from the wave damper and is 1/8 away wavelength between probes 1-8. Water level fluctuation data is processed to obtain wave height in each wave probe using zero up crossing method. To test the performance of this wave damper, performed tests and their reflection coefficients are compared with other theoretical and experimental models. Test laboratory is carried out to acquire wave data and numerical data processing is carried out for clarify results. Wave damping experiments carried out in the laboratory produce damping relatively good waves where the reflection coefficient values obtained on average are below 0.2 (Hr/Hi) will but the performance of the wave damper in the laboratory is not as effective as the damper using chunk media stone so further development and analysis is needed.